Dysphagia caused by an aberrant right subclavian artery - Hassan, Radhiana; Md Ralib@Md Raghib, Ahmad Razali; Wan Leman, Wan Ishlah (Faculty of Medicine, International Islamic University Malaysia, 2011)
An aberrant right subclavian artery is the commonest aortic arch anomaly. Majority of them were asymptom- atic. An aberrant subclavian artery is a rare cause of dysphagia in adults. This condition is also known as dys- phagia lusoria. We report a case of dysphagia in a 49-year-old woman from an aberrant right subclavian artery. Diagnosis of her condition was made with barium swallow and MDCT (multidetector computed tomography) scan. She was managed conservatively.